Cancer-associated fibroblasts promote drug resistance in ALK-driven lung adenocarcinoma cells by upregulating lipid biosynthesis - Daum, Ann-Kathrin; Schlicker, Lisa; Schneider, Marc; Muley, Thomas; Klingmüller, Ursula; Schulze, Almut; Thomas, Michael; Christopoulos, Petros; Sültmann, Holger (Cancer & metabolism, 2025)
Background: Targeted therapy interventions using tyrosine kinase inhibitors (TKIs) provide encouraging treatment responses in patients with ALK-rearranged lung adenocarcinomas, yet resistance occurs almost inevitably. In addition to tumor cell-intrinsic resistance mechanisms, accumulating evidence suggests that cancer-associated fibroblasts (CAFs) within the tumor microenvironment contribute to therapy resistance. This study aimed to investigate CAF-driven molecular networks that shape the therapeutic susceptibility of ALK-driven lung adenocarcinoma cells. Methods: Three-dimensional (3D) spheroid co-cultures comprising ALK-rearranged lung adenocarcinoma cells and CAFs were utilized to model the tumor microenvironment. Single-cell RNA sequencing was performed to uncover transcriptional differences between TKI-treated homotypic and heterotypic spheroids. Functional assays assessed the effects of CAF-conditioned medium and CAF-secreted factors on tumor cell survival, proliferation, lipid metabolism, and downstream AKT signaling. The therapeutic potential of targeting metabolic vulnerabilities was evaluated using pharmacological inhibition of lipid metabolism and by ferroptosis induction. Results: CAFs significantly diminished the apoptotic response of lung tumor cells to ALK inhibitors while simultaneously enhancing their proliferative capacity. Single-cell RNA sequencing identified lipogenesis-associated genes as a key transcriptional difference between TKI-treated homotypic and heterotypic lung tumor spheroids. CAF-conditioned medium and the CAF-secreted factors HGF and NRG1 activated AKT signaling in 3D-cultured ALK-rearranged lung tumor cells, leading to increased de novo lipogenesis and suppression of lipid peroxidation. These metabolic adaptations were critical for promoting tumor cell survival and fostering therapy resistance. Notably, both dual inhibition of ALK and the lipid-regulatory factor SREBP-1, as well as co-treatment with ferroptosis inducers such as erastin or RSL3, effectively disrupted the CAF-driven metabolic-supportive niche and restored sensitivity of resistant lung tumor spheroids to ALK inhibition. Conclusions: This study highlights a critical role for CAFs in mediating resistance to ALK-TKIs by reprogramming lipid metabolism in ALK-rearranged lung cancer cells. It suggests that targeting these metabolic vulnerabilities, particularly through inhibition of lipid metabolism or induction of ferroptosis, could provide a novel therapeutic approach to overcome resistance and improve patient outcomes.
Gesehen am 20.10.2025